2009
DOI: 10.1590/s1678-91992009000100011
|View full text |Cite
|
Sign up to set email alerts
|

Antivenom action on renal effects induced by Thalassophryne nattereri venom

Abstract: ABSTRACT:Thalassophryne nattereri (niquim) is a venomous fish responsible for numerous accidents involving fishermen in northern and northeastern Brazil. The aim of the present investigation was to evaluate the action of antivenom on renal effects caused by Thalassophryne nattereri venom. Isolated kidneys of Wistar rats were perfused with a previously dialyzed Krebs-Henseleit solution containing 6 g% bovine serum albumin. The antivenom action was studied through perfusion pressure (PP), renal vascular resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Changes in kidney function include increase in renal parameters such as perfusion pressure, vascular resistance, glomerular filtration rate and urinary flow. Renal changes observed in this study corroborate earlier reports with other animal venoms which registered similar changes in renal function (24,25).…”
Section: Discussionsupporting
confidence: 93%
“…Changes in kidney function include increase in renal parameters such as perfusion pressure, vascular resistance, glomerular filtration rate and urinary flow. Renal changes observed in this study corroborate earlier reports with other animal venoms which registered similar changes in renal function (24,25).…”
Section: Discussionsupporting
confidence: 93%
“…We may suggest that the venom affects directly kidney cells by causing the release of vasoactive factors and the decrease of electrolyte transport [10,11]. …”
Section: Reviewmentioning
confidence: 99%
“…Additionally we demonstrated that T. nattereri venom (0.3, 1.0, and 3.0 μg/mL) promoted increase in perfusion pressure and renal vascular resistance in mice with hyalin casts inside all tubules and proteinaceous material in the urinary space. We may suggest that the venom affects directly kidney cells by causing the release of vasoactive factors and the decrease of electrolyte transport [ 10 , 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…Although fish envenomation is frequent in Brazil, only pre-clinical studies of neutralization with anti-venom antibodies in experimental models were performed [9,[19][20][21][22], and until now there are no commercially available antisera for human victims. The objective of this work was to produce an antiserum in mice composed of polyclonal IgG antibodies against multiple toxins from the venoms of the most medically important fish species in Brazil such as Thalassophryne nattereri, Scorpaena plumieri, Potamotrygon gr.…”
Section: Introductionmentioning
confidence: 99%